Critérios para análise de limites e potencialidades da sustentabilidade de fontes de energia: um estudo da cadeia produtiva das pequenas centrais hidrelétricas no Brasil - Nowakowski, Geórgia Alana Andréas (2015)
This research study has as a theme: Small Hydro Power Plants (SHP). Its overall objective is to identify the main limits and potential sustainabilities of the productive chain of power plants in Brazil to the context of environmental, social, economic and institutional dimensions. The theoretical framework includes concepts that concern: the production chain, the Actor-Network Theory, renewable energy sources (specifically hydroelectricity) and the determinants of competitiveness. For the identification of limits and potential, mapping of the production of SHP chain structure was carried out; as well as the description of the current landscape of the SHP in the country. They were then studied in more depth. The five steps that make up the chain being: natural resource, generation, transmission, distribution and commercialization. Next, five criteria were used: importance, likelihood, timeliness, effect and scope; in order to classify the factors identified in each step. Finally, by multiplying the numerical index assigned to the criteria; the significance index (SI) was obtained, which was used to frame the final significance of the aspects by: less significant, significant and very significant. Regarding research methodology; it can be classified as: exploratory and applied. The data used was secondary and was used as qualitative analysis. As a result, we identified 20 potential limits and 17 related to the production chain of power plants in Brazil, and of these 37 items, 8 were classified as very significant, according to the criteria established for the IS. With regard to the main search result, it appears that, although there are significant potential for the development of SHP in the national energy matrix (hydropower potential of river basins, their ability to act as regional development vector, consolidation of turbines and generators manufacturers, and free access), some hurdles in the production chain must be worked out, such as interference in the migration and reproduction of continental fish fauna, inequality in the distribution of electricity, and the legal and technical aspects related to the environment and the commercialization of energy.